Architectural design quality and social sustainability in building certification systems - Ing. arch. Lucia Oberfrancová (Slovak University of Technology, Faculty of Architecture and Design, 2021)
The main objective of the study is to examine to what extent the architectural design quality and social sustainability are taken into account in building certification systems. The following most commonly used building assessments in Europe (focus on Germany, Slovakia and Czech Republic) have been investigated: BREEAM, LEED, CESBA, LEVEL(s), DGNB, BNB, BNK, NaWoh, SBToolCZ and WELL. After extensive research of chosen certification systems and various sources on topics such as conditions of well-being, sociocultural indicators, assessment of social performance of sustainable buildings and design quality assessment, the main social and architectural design quality aspects were determined and used for further analysis and final evaluation. Studied aspects are divided into the following categories: user satisfaction and quality of life (building-related), sustainable and healthy lifestyle (building-related), architecture – design quality (building-related), innovation and social responsibility (external). The article contains a summary of results with overall evaluation and comparison of certification systems including weighting of studied categories in selected building assessments. Furthermore, indicators used in building certifications associated with the quality of life and the quality of architectural expression and their weighting are described and presented.